From normative imaginary reality of the Network of Emergency Care - Almeida, Adriana C.; Gusmão Filho, Fernando A. R.; Caldas Junior, Arnaldo F.; Vidal, Suely A.; Campello, Reginaldo I. C. (Medicina (Ribeirao Preto), 2015)
Study design: a case study. Objective: To analyze the Emergency Care Network from the perspective of the Mobile Emergency Care Service of the Metropolitan Recife (SAMU). Material and Method: a case study with multiple units of analysis. The object of the study was the SAMU and the units of analysis were the components: promotion, prevention and health surveillance; organization and governance of the network. We opted for the triangulation of methods and sources, using semistructured interviews with 57 professionals working in this service; direct observation and official documents (database, ordinances and reports). For the analysis of qualitative data we used the technique of condensing meanings and quantitative, the average frequency of events. Results: The profile of the professionals interviewed shows that 53% were male, 65%, had graduated less than 12 years, a little more than half worked in the SAMU for less than 2 years and 77% had temporary employment through contracts with the municipalities. According to the interviewees there are strategies of promotion and prevention, but one cannot see changes in the epidemiological and demographic profile as a result of the implementation of these strategies. There is an inadequate distribution of health equipment; low health coverage of the population (50% of PSF coverage / ESF and deficit of 3,089 hospital beds) and lack of coordination between the state regional steering committee of the care system emergencies.Conclusion: The lack of information on care management in the emergency area, promotion and prevention strategies generates discontinuity in the process of surveillance, added by communication failures across the SAMU service network. Therefore, there is a deficit and inadequacy of health coverage. The lack of integration between services, the difficulty of access and the patient continuity on the treatment demonstrates the inadequate governance of the service network to the emergency room